Antiproliferative Activity and Antioxidant Potential of Extracts of Garcinia gardneriana - Simone da Cunha Demenciano; Magalli Costa Barbosa Lima e Silva; Caroline Almeida Farias Alexandrino; Wilson Hino Kato Junior; Patrícia de Oliveira Figueiredo; Walmir Silva Garcez; Raquel Pires Campos; Rita de Cássia Avellaneda Guimarães; Ulana Chaves Sarmento; Danielle Bogo (Molecules, 2020)
The aim of this study was to evaluate the antiproliferative activity, the antioxidant potential, and the chemical profile obtained from the whole fruit and from leaves of Garcinia gardneriana, a fruit tree from Brazilian Cerrado. To determine in vitro antiproliferative activity, the following neoplastic cell lines were considered, along with an immortalized nontumor cell line. The antioxidant potential was determined, and the evaluation of antiradical air activity was performed. The levels of vitamin C and carotenoids were determined. The chemical profile was analyzed by high-performance liquid chromatography coupled to a diode array detector and a mass spectrometer using electrospray ionization interface. The chloroform fraction of the leaf showed antioxidant activity. The vitamin C content had lower values in fruits and higher in leaves. The content of carotenoids for fruits and leaves was expressive. The ethanolic extract and the hexane and chloroform fractions of fruits were active in all neoplastic lines tested. The leaves showed cytotoxic activity in the hexane fraction in the breast carcinoma line. The analysis of data obtained verified the presence of dimers, monomers, and tetramers of hexoses, polycarboxylic acids, xanthones, flavonoids, biflavonoids, and benzophenones.